Pendampingan Belajar Menghafal Surat-Surat Pendek dengan Metode Muroja’ah di SDN 2 Sidoharjo Kecamatan Pulung Ponorogo - Dwi Astutik (Institut Agama Islam Sunan Giri Ponorogo, 2025)
At SDN 2 Sidoharjo, the Pulung Ponorogo sub-district has an excellent program, which is memorizing short surahs in the Qur'an. The memorization program starts from grade 1 to grade 6. With this program KPM insuri group 8 will provide assistance in the process of memorizing activities. The purpose of this assistance is to train students' memory and facilitate how to read the Qur'an from an early age, as well as foster a sense of love for the Qur'an. In carrying out this assistance the method used is Asset Based Community Development (ABCD). Efforts made to improve the ability to memorize the Qur'an at SDN 2 Sidoharjo are: using the muroja'ah method. The result of this assistance is that children can increase their memorization of short letters and love the Qur'an more and more. In the muraja'ah mentoring method, it helps students achieve the goals of memorizing that are programmed by the school, helping students memorize the Al-Quran correctly and precisely according to makhraj and the tajwid. Then the application of the muroja'ah memorization method makes students fluent, skilled and able to improve their ability to memorize short surahs quickly